The Role of Organizational Commitment Moderating Factors Affecting Budget Absorption - Sopiyah, Siti; Sriyono, Sriyono; Sukmono , Rita Ambarwati (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study aims to prove the influence of budget planning, human resource competence, and utilization of information technology on budget absorption with organizational commitment as a moderating variable. Using a quantitative research method, purposive sampling was used in the sample selection process, 185 respondents, including the Budget Implementation Coordinator (KPA), Budget Implementation Coordinator (PPK), Budget Implementation Coordinator (PPSPM), Head of Planning Sub-Division and Expenditure Treasurer in 37 work units under the Surabaya High Religious Court. The hypothesis was tested with SEM-PLS by SMART PLS 4.1.0.9. The results showed that budget planning does not affect budget absorption, human resource competence, and information technology, which significantly impacts budget absorption. Organizational commitment as a moderating variable does not moderate the impact of budget planning and human resource competence on budget absorption, but it does moderate the effect of information technology utilization on budget absorption.